PENGARUH KUALITAS PELAYANAN, SANKSI PERPAJAKAN DAN KESADARAN WAJIB PAJAK PADA KEPATUHAN WAJIB PAJAK - Adiputra, I Putu Eka; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
The aim of this study is to determine the influences of the service quality, tax penalties, and the consciousness of taxpayers toward the compliance of groundwater taxpayers in the Regional Revenue Bureau of Badung Regency. The sample used in this study were 92 active groundwater taxpayers who have been registered in the bureau during 2011 – 2015, the number of which was determined by the Slovin Formula. The data collection was conducted through questionnaires and the data analysis was undertaken based on regression analysis. The result of this study shows that the service quality influences positively the compliance of groundwater taxpayers, that the tax penalties also affects the compliance of groundwater taxpayers positively, and that the consciousness of taxpayers affects the compliance of groundwater taxpayers as well.
Keywords: compliance of taxpayers, service quality, tax penalties, consciousness of taxpayers